Analysing the Art of Service Quality and Customer Satisfaction of Digital Banking Services: A SEM Approach - Bhuvaneswari, C. M.; Maruthamuthu, K. (International Review of Management and Marketing, 2024)
Given that India is among the countries with the fastest-growing digital banking service providers globally, the purpose of this research is to examine the relationship between service quality and customer satisfaction when using digital banking through the use of a structural equation model. An organised set of survey questions was created in order to gather information from respondents in India. The study employed a stratified sampling technique to choose possible participants. 232 completed and useable questionnaires were chosen from the distribution to be analysed using AMOS-structural equation modelling (SEM). The findings demonstrated that consumer satisfaction with digital banking is positively and significantly impacted by all of the components of service quality—tangibility, reliability, responsiveness, assurance, and empathy. Customer satisfaction is very strongly impacted by response. Additionally, it has been determined that tangibility has less of an impact on consumer satisfaction. The findings also indicate that digital banking service providers should focus on improving all facets of service quality, with a focus on timeliness and reliability, in order to boost consumer satisfaction. When providing services to end users and clients of digital banking, researchers, banking authorities, legislators, and financial organisations will need to consider a number of conclusions from this study. Additionally, this implication aids banks in comprehending and creating policies and strategies to enhance India's digital banking services.